Elastoplastic fracture behavior of Caragana korshinskii Kom. branches: a discrete element model for biomechanical insights into shrub resource utilization - Su, Qiang; Ma, Xuejie; Liu, Wenhang; Zhang, Jianchao; Yu, Zhihong; Liu, Zhixing (Frontiers in Plant Science, 2025)
IntroductionThe interaction between Caragana korshinskii Kom. (CKB) branches and crushing machinery is complex, requiring a detailed mechanical model to effectively describe the fracture characteristics of CKB during crushing. This study aims to develop such a model using the discrete element method to simulate the elastoplastic fracture behavior of CKB.MethodsA mechanical model for CKB was established based on its fracture mechanical characteristics. The model incorporates elastoplastic stages, including elastic, elastoplastic, and fully plastic phases during stem crushing. A parameter calibration method was employed, combining physical experiments with simulation experiments to refine the discrete element model. The key binding parameters of the model were optimized to best simulate the mechanical properties of CKB under various loading conditions.ResultsThe optimal binding parameters for the flexible discrete element model were identified as: normal stiffness of 3.67×1010 N·m-3, shear stiffness of 3.42×1010 N·m-3, critical normal stress of 6.57×108 Pa, and a binding radius of 0.78 mm. The model successfully replicated the elastic stage force-displacement curve in compression tests with an error of only 0.24%. The discrepancies between simulated and actual fracture forces were 2.79% for compression, 4.68% for bending, 4.14% for shear, and 8.64% for tensile tests, showing good agreement with experimental results.DiscussionThe developed model accurately simulates the elastoplastic fracture behavior of CKB under compression, bending, and shear, providing valuable insights into the crushing mechanism of CKB. The calibration process demonstrated that the proposed DEM model can be an effective tool for exploring and optimizing the crushing process of CKB.